2019
DOI: 10.1002/jgh3.12202
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage control during gastric endoscopic submucosal dissection: Techniques using uncovered knives

Abstract: Since the last decade, endoscopic submucosal dissection (ESD) has been used as the standard treatment for superficial gastrointestinal neoplasms. Trainees learning ESD frequently encounter difficulties such as vascularity, peristalsis, and fibrosis during the procedure. Because individual vascularity differs, it generally cannot be consistently avoided. Given that massive hemorrhages can prolong the procedure time and diminish treatment efficacy and that insufficient vessel handling may also increase postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Bleeding is one of the most common complications associated with ESD, as intraprocedural bleeding interferes with precise endoscopic resection under a clear view of the operating field, which can lead to longer procedure times or an increase in the frequency of complications, such as perforation. 4 The incidence rates of immediate and delayed bleeding associated with gastric ESD are approximately 22% and 4.5%-5.5%, respectively. [5][6][7] A recent meta-analysis showed that the incidence rates of immediate and delayed bleeding associated with colorectal ESD are 0.82% and 1.7%, respectively.…”
Section: Diode Laser-can It Replace the Electrical Current Used In Endoscopic Submucosal Dissection? (With Video)mentioning
confidence: 99%
“…Bleeding is one of the most common complications associated with ESD, as intraprocedural bleeding interferes with precise endoscopic resection under a clear view of the operating field, which can lead to longer procedure times or an increase in the frequency of complications, such as perforation. 4 The incidence rates of immediate and delayed bleeding associated with gastric ESD are approximately 22% and 4.5%-5.5%, respectively. [5][6][7] A recent meta-analysis showed that the incidence rates of immediate and delayed bleeding associated with colorectal ESD are 0.82% and 1.7%, respectively.…”
Section: Diode Laser-can It Replace the Electrical Current Used In Endoscopic Submucosal Dissection? (With Video)mentioning
confidence: 99%
“…During ESD, control of complications is important, as is a high resection rate. Reduced intraoperative bleeding provides better visualization of the submucosal layer, allowing the operator to complete gastric ESD without stress, thereby improving ESD performance 37 38 39 . Akahoshi et al 40 reported that in most cases of gastric ESD, hemostasis was achieved using the CC alone; the rate of massive intraoperative bleeding was 0 %.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, for vessels with diameters 2 mm or for patients at an increased risk of hemorrhage, hemostatic forceps is preferred to ensure complete hemostasis by thermocoagulation in the soft coagulation mode (effect 4-5, 80 W; VIO300D). 6 After grasping with the forceps, it is important to gently pull back the vessel to avoid transmission of current in the deeper layers of the GI wall. Since the colonic walls are thinner as compared to the gastric wall, a smaller coagulation forceps with lower opening width (4 vs. 5 and 6.5 mm) is preferred.…”
Section: Hemostasismentioning
confidence: 99%